Analysis of aerosol spreading in a German Inter City Express (ICE) train carriage. (15th August 2022) - Schmeling, Daniel; Kühn, Matthias; Schiepel, Daniel; Dannhauer, Axel; Lange, Pascal; Kohl, Andreas; Niehaus, Konstantin; Berlitz, Tim; Jäckle, Marcel; Kwitschinski, Thomas; Tielkes, Thorsten
Abstract: This paper focuses on the propagation of aerosols in a rolling stock passenger compartment. Extensive measurements were carried out in our stationary test vehicle DIRK, an ICE 2 rail car, operated in a climate chamber. It is shown that the propagation of aerosols only occurs for a distance of a few seat rows. Furthermore, the maximum percentage of particles exhaled by a passenger and inhaled by another passenger is less than 0.35%. A mouth-nose-protection (surgical mask) at the aerosol source reduces this value to a maximum of 0.25%. Moreover, the use of a mouth-nose-cover reduced the propagation lengths. Here, only the effect of the mask at the source was considered, a further reduction of inhaled aerosols will be achieved when the receivers also wear masks. It is concluded that, for this type of passenger coach, the indirect propagation of aerosols, i.e., via the HVAC system, is nearly irrelevant compared to the direct propagation from one passenger to another. However, there is a non-zero aerosol transport via the HVAC system, resulting in local inhaled particles far away from the source of around 0.015–0.026%, which is more than one order of magnitude lower than on the most highly contaminated seats. Graphical abstract: Image 1 Highlights: Experimental study of aerosol dispersion in a long-distance ICE train carriage. Application of tracer-gas and particle concentration for multiple configurations. Spreading occurs over a restricted space and is reduced by wearing a mask. Direct transmission is more than one order of magnitude larger than indirect one. Decay time-constant of local particle concentration is maximal 5 min.